Routine laboratory diagnosis of chromosome aberrations in multiple myeloma - Chin, Yuet-Meng; Zakaria, Zubaidah (International Journal of Research in Medical Sciences, 2017)
Multiple Myeloma (MM) is a Plasma Cell (PC) malignancy characterized by proliferation of differentiated B cells mainly in the bone marrow. Genetic abnormalities are powerful prognostic factors in MM for risk stratification and therapeutic strategies. The standard diagnostic tests to detect genetic abnormalities in MM include Conventional Cytogenetic Analysis (CCA) and Interphase Fluorescence In Situ Hybridization (FISH). Due to the low proliferative activity of the abnormal clone, only 30-50% of newly diagnosed MM demonstrate an abnormal karyotype by CCA. CCA is a biological test which requires dividing cells for analysis. The t(4;14) translocation which carries a poor prognosis is cryptic and cannot be detected by CCA. These limitations were overcome partly by the incorporation of interphase FISH as a routine diagnostic test in MM. There is an international consensus that FISH should be performed in all newly diagnosed MM to detect high-risk genetic abnormalities. FISH testing must be done on purified PCs or by simultaneous labeling of cytoplasmic immunoglobulin light chain to allow identification of PCs. The minimum essential abnormalities to test for are t(4;14), t(14;16) and del(17)(p13). However, there is no consensus on the optimal protocol for CCA and interphase FISH. We review here the types of chromosomal aberrations found in MM, the prognostic significance of these abnormalities, methodologies in CCA to improve on the low yield of abnormal karyotypes, and protocols in interphase FISH.